Accelerated Muscle Deoxygenation in Aerobically Fit Subjects During Exhaustive Exercise Is Associated With the ACE Insertion Allele - Gasser, Benedikt; Franchi, Martino V.; Ruoss, Severin; Frei, Annika; Popp, Werner L.; Niederseer, David; Catuogno, Silvio; Frey, Walter O.; Flück, Martin (Frontiers in Sports and Active Living, 2022)
Introduction The insertion/deletion (I/D) polymorphism in the gene for the major regulator of vascular tone, angiotensin-converting enzyme-insertion/deletion (ACE-I/D) affects muscle capillarization and mitochondrial biogenesis with endurance training. We tested whether changes of leg muscle oxygen saturation (SmO2) during exhaustive exercise and recovery would depend on the aerobic fitness status and the ACE I/D polymorphism. Methods In total, 34 healthy subjects (age: 31.8 ± 10.2 years, 17 male, 17 female) performed an incremental exercise test to exhaustion. SmO2 in musculus vastus lateralis (VAS) and musculus gastrocnemius (GAS) was recorded with near-IR spectroscopy. Effects of the aerobic fitness status (based on a VO2peak cutoff value of 50 ml O2 min−1 kg−1) and the ACE-I/D genotype (detected by PCR) on kinetic parameters of muscle deoxygenation and reoxygenation were assessed with univariate ANOVA. Results Deoxygenation with exercise was comparable in VAS and GAS (p = 0.321). In both leg muscles, deoxygenation and reoxygenation were 1.5-fold higher in the fit than the unfit volunteers. Differences in muscle deoxygenation, but not VO2peak, were associated with gender-independent (p > 0.58) interaction effects between aerobic fitness × ACE-I/D genotype; being reflected in a 2-fold accelerated deoxygenation of VAS for aerobically fit than unfit ACE-II genotypes and a 2-fold higher deoxygenation of GAS for fit ACE-II genotypes than fit D-allele carriers. Discussion Aerobically fit subjects demonstrated increased rates of leg muscle deoxygenation and reoxygenation. Together with the higher muscle deoxygenation in aerobically fit ACE-II genotypes, this suggests that an ACE-I/D genotype-based personalization of training protocols might serve to best improve aerobic performance.